Аккредитация организаций, выполняющих неразрушающий контроль, как необходимое условие доступа предприятий Украины к международным рынкам промышленных товаров и услуг - Хорло, Н. Ф. (Национальный технический университет "Харьковский политехнический институт", 2019)
Выполнен обзор международной системы аккредитации, обеспечивающей подтверждение компетенции организаций, выполняющих неразрушающий контроль промышленных изделий как органов оценки соответствия. Рассмотрены механизмы, обеспечивающие взаимное признание результатов аккредитации участниками международного рынка товаров и услуг. Определены нормативные требования к процедуре аккредитации.

A review of the international accreditation system was carried out, providing confirmation of the competence of organizations performing non-destructive testing of industrial products as conformity assessment bodies. The mechanisms that ensure mutual recognition of the results of accreditation by participants of the international market of goods and services are considered. Defined regulatory requirements for the accreditation procedure.
Accreditation of organizations providing non-destructive testing services, as a necessary condition for access of Ukrainian enterprises to international markets for industrial products and services
Keywords: система аккредитации; международный рынок; accreditation system; international market